Diagnosis of Biliary Strictures Using Probe-Based Confocal Laser Endomicroscopy under the Direct View of Peroral Cholangioscopy: Results of a Prospective Study (with Video). (31st December 2020) - Tanisaka, Yuki; Ryozawa, Shomei; Nonaka, Kouichi; Yasuda, Masami; Fujita, Akashi; Ogawa, Tomoya; Mizuide, Masafumi; Tashima, Tomoaki; Araki, Ryuichiro
Abstract : Background . The accurate diagnosis of biliary strictures remains problematic. The aim of the present study was to prospectively evaluate the clinical utility of probe-based confocal laser endomicroscopy (pCLE) under the direct view of peroral cholangioscopy (POCS) for the diagnosis of biliary strictures. Methods . Consecutive patients with biliary strictures were included. We investigated sensitivity, specificity, and accuracy to diagnose malignancy for (1) ERCP alone, (2) POCS, (3) pCLE under the direct view of POCS, and (4) tissue sampling under the direct view of POCS. Results . A total of 30 patients (17 with malignant lesions) were prospectively enrolled. (1) ERCP alone showed 88.2% sensitivity, 46.2% specificity, and 70% (95% confidence interval (CI), 52.1%–83.3%) accuracy. (2) POCS showed 100% sensitivity, 76.9% specificity, and 90% (95% CI, 74.4%–96.5%) accuracy. (3) pCLE under the direct view of POCS showed 94.1% sensitivity, 92.3% specificity, and 93.3% (95% CI, 78.7%–98.8%) accuracy. (4) Tissue sampling under the direct view of POCS showed 82.4% sensitivity, 100% specificity, and 90% (95% CI, 74.4%–96.5%) accuracy. Conclusions . pCLE under the direct view of POCS provided highly accurate and sensitive characterization of biliary strictures and showed the potential for more diagnostic reliability and reduction of delays in diagnosis. This trial was registered at UMIN (registration number: UMIN000033801 ).